التسويق الشبكي في شركة HNI : ‏ ‏ دراسة فقهية تحليلية - Muhammad Azzam Ismail (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Network marketing makes it easier for companies to sell their products where they depend on costumers who also act as sales agents. Muslim scholars adopted three opinions regarding the ruling of network marketing: absolutely haram, mubah, and an opinion that prefers to look into the details of each case independently. Nevertheless, the three differing opinions create confusion and ambiguity for both companies and consumers. The researcher analyzed the extent to which the suitability of the HNI's network marketing, an Indonesian network marketing company, complies with the rules that had been laid by scholars. This study uses the qualitative method and analysis. Based on the analysis, there are at least three syubhat elements contained in network marketing of HNI. They include gambling, usury, and gharar. The researcher recommends that the company omits the registration fees which clients have to pay at the time of joining the company because such fees basically form the foundation for syubhat. The study hopes to put to rest the moral confusion on network maketing.